2018
DOI: 10.1534/g3.118.200030
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variation Among and Within SixJuglansSpecies

Abstract: Genomic analysis in Juglans (walnuts) is expected to transform the breeding and agricultural production of both nuts and lumber. To that end, we report here the determination of reference sequences for six additional relatives of Juglans regia: Juglans sigillata (also from section Dioscaryon), Juglans nigra, Juglans microcarpa, Juglans hindsii (from section Rhysocaryon), Juglans cathayensis (from section Cardiocaryon), and the closely related Pterocarya stenoptera. While these are ‘draft’ genomes, ranging in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 91 publications
2
68
0
Order By: Relevance
“…The initial step in the transition from conventional breeding to genomics-assisted breeding is the discovery of DNA sequence variation. Stevens et al (2018) re-sequenced 27 walnut accessions selected as either representing the UC Davis WIP founders or showing interesting phenotypes for traits of interest in walnut (e.g., kernel colour; Mart ınez-Garc ıa et al, 2017). The discovery panel is mostly comprised of US accessions, but also includes wild germplasm and cultivars introduced to the UC Davis WIP from other leading countries in global walnut production, namely China, France, Afghanistan, Japan and Bulgaria (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial step in the transition from conventional breeding to genomics-assisted breeding is the discovery of DNA sequence variation. Stevens et al (2018) re-sequenced 27 walnut accessions selected as either representing the UC Davis WIP founders or showing interesting phenotypes for traits of interest in walnut (e.g., kernel colour; Mart ınez-Garc ıa et al, 2017). The discovery panel is mostly comprised of US accessions, but also includes wild germplasm and cultivars introduced to the UC Davis WIP from other leading countries in global walnut production, namely China, France, Afghanistan, Japan and Bulgaria (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the mapped reads, 17 800 528 SNPs distributed over 9042 scaffolds were identified (available at https://www.ha rdwoodgenomics.org/Genome-assembly/2209433). The number of SNPs was then reduced by almost 50% (9 582 656 variants) after applying quality filters (Figure 1; Stevens et al, 2018). Following Affymetrix (now part of Thermo Fisher Scientific, Waltham, MA) recommendations (see Figure 1), we selected 2 412 872 SNPs potentially suitable for incorporation on the SNP array, by discarding polymorphisms with complex genotypic patterns (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…regia genome sequencing, a second homologue of PPO ( JrPPO2 ) was discovered (Martínez‐García et al , ) and this was subsequently identified in several additional Juglans species using comparative genomics resources (Stevens et al , ). In both studies, the JrPPO1 and JrPPO2 transcripts were differentially expressed, with JrPPO1 expressed in a wide range of green tissues and JrPPO2 expressed in callus, catkins, vegetative buds, pistillate flower, immature hull, and hull cortex but not in hull tissue, immature fruit, and leaves (Martínez‐García et al , ; Stevens et al , ). Therefore, differences in tissue‐based expression of PPO genes might be an explanation for the detection of only one melanin band in immature walnut hulls.…”
Section: Discussionmentioning
confidence: 99%